A Merovingian commentary on the four gospels: (Pseudo-Theophilus, CPL 1001) - Hen, Yitzhak (Revue des études augustiniennes, 2003)
The commentary on the four Gospels, first published by Marguerin de la Bigne in 1575, was attributed by its first editor to the second-century author Theophilus of Antioch, and since then scholars were mainly obsessed with justifying or refuting this attribution. Various philological and grammatical arguments were used in the past by both sides in order to prove their point, yet none of the scholars who discussed this commentary had ever considered seriously the possibility that it is probably an early medieval composition. This paper suggests that the Pseudo-Theophilus commentary on the four Gospels is a product of the intellectual and cultural activity which characterised late sixth-and early seventh-century Gaul. This, of course, is impossible to prove unequivocally before some more new evidence is unearthed, but several features of the commentary itself, such as its sources, its style, as well as its circulation and influence, point to that direction.